2013
DOI: 10.1177/230949901302100307
|View full text |Cite
|
Sign up to set email alerts
|

Ropivacaine versus Bupivacaine for 3-in-l Block during Total Knee Arthroplasty

Abstract: Ropivacaine and bupivacaine showed similar anesthetic and analgesic effects, but the former had a significantly faster onset time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
1
5
0
1
Order By: Relevance
“…Meftah M et al 27 combined a femoral nerve block and patient-controlled epidural analgesia; they used bupivacaine for the block and infiltration, while others 5 , 25 , 26 , 28 , 29 used ropivacaine. Theodosiadis P et al compared the efficacy and safety of ropivacaine and bupivacaine for a 3-in-1 block during total knee arthroplasty and found that ropivacaine and bupivacaine had similar analgesic effects 31 . Muldoon T et al determined that ropivacaine was associated with slightly higher pain scores than bupivacaine was, but the mean value of the difference might not reflect a significant clinical difference 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Meftah M et al 27 combined a femoral nerve block and patient-controlled epidural analgesia; they used bupivacaine for the block and infiltration, while others 5 , 25 , 26 , 28 , 29 used ropivacaine. Theodosiadis P et al compared the efficacy and safety of ropivacaine and bupivacaine for a 3-in-1 block during total knee arthroplasty and found that ropivacaine and bupivacaine had similar analgesic effects 31 . Muldoon T et al determined that ropivacaine was associated with slightly higher pain scores than bupivacaine was, but the mean value of the difference might not reflect a significant clinical difference 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The local anesthetic used was ropivacaine, which has low toxicity, a rapid onset, and a prolonged anesthetic effect. 16,17 ISB was performed before general anesthesia induction using the ultrasound-guided "in-plane" technique with the patient in the supine position by an experienced anesthesiologist. A 21-gauge SonoPlex Stim needle (Pajunk Medical Systems, Tucker, GA) was inserted into the interscalene groove.…”
Section: Nerve Block and Surgical Techniques And Postoperative Carementioning
confidence: 99%
“…who performed 3-in-1 block following TKA and compared ropivacaine (398 min) with bupivacaine (367 min) ( P = 0.62). [ 6 ] This difference from our study could be due to the blind technique of block administration (3-in-1 block) versus ultrasound-guided FNB and the use of dexmedetomidine with ropivacaine to prolong the analgesia.…”
Section: Discussionmentioning
confidence: 64%